2016
DOI: 10.1097/gox.0000000000001048
|View full text |Cite
|
Sign up to set email alerts
|

Eight-strand Cross-locked Cruciate Flexor Tendon Repair Using Double-stranded Suture: A Description of the Surgical Technique

Abstract: Summary:This article describes a technique for improved repair of digital flexor tendon laceration. Eight-strand cross-locked cruciate repair using 4-0 caliber double-stranded suture is not bulky and has a smooth configuration for tendon gliding. Additionally, it has sufficient strength for early postoperative active motion exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The sixstrand modified Savage technique and eight-strand crosslocked cruciate repair require more needle reversal than Yoshizu cross-lock repair. 4,14 The load to a 2-mm gap is used to measure clinical failure because gaps larger than 2 mm have been associated with significant deteriorations in patient outcomes (caused by adhesions). 17, 18 Urbaniak et al reported that active flexion under mild resistance can impart a force of 10 N; this increases to 17 N when resistance is moderate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sixstrand modified Savage technique and eight-strand crosslocked cruciate repair require more needle reversal than Yoshizu cross-lock repair. 4,14 The load to a 2-mm gap is used to measure clinical failure because gaps larger than 2 mm have been associated with significant deteriorations in patient outcomes (caused by adhesions). 17, 18 Urbaniak et al reported that active flexion under mild resistance can impart a force of 10 N; this increases to 17 N when resistance is moderate.…”
Section: Discussionmentioning
confidence: 99%
“…The six-strand modified Savage technique and eight-strand cross-locked cruciate repair require more needle reversal than Yoshizu cross-lock repair. 4 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, other 8-strand tendon repair techniques were introduced, such as the new half-hitch loop suture, 27 surface locking Kessler techniques, 28 and 8-strand cross-locked cruciate repair using a double-stranded suture. 29 Despite several biomechanical studies, there are no reports that detail clinical outcomes using 8-strand sutures and early active mobilization. These techniques have relatively complex configurations.…”
Section: Discussionmentioning
confidence: 99%
“… 13 17 Additionally, to maximize the success of tendon repair, it is generally recommended that a locking technique be used rather than a grasping technique. 18 21 The extremes of these principles have even led to the development of steel devices 22 and use of 8-stranded repair techniques, 14 which demonstrate a predictable increase in strength during ex vivo testing. While such techniques may increase strength, it is often done so at the cost of additional bulk and introduction of more foreign material into the body.…”
Section: Introductionmentioning
confidence: 99%